Elevator Cabin Decontamination With ACTIVE Particle Control™ Technology - Ereth, Mark; Wagoner, Tracy; Blevins, Mark; Hess, Donald (Frontiers in Public Health, 2021)
Effectively reducing contamination and aerosolized bioburden may limit the risk of disease transmission in closed settings when social distancing is not possible. Unlike uncontrolled ionization and oxidation devices ACTIVE Particle Control™ conditions particles in a highly controlled fashion which provides effective air purification without the generation of ozone or other toxic by-products. The purpose of this study was to determine the impact of ACTIVE Particle Control™ on elevator cabin particle load compared to standard ventilation. The intervention trial utilized particle mass tools to determine the difference in particle clearance between standard elevator cabin ventilation and ACTIVE Particle Control™ technology. Cabin particulate contaminants were significantly reduced using ACTIVE Particle Control™ technology in an operating elevator.